Controlling Environment and Contact Materials to Optimize Ohmic Microrelay Lifetimes. Issue 1659 (10th February 2014) - Brand, Vitali; Baker, Michael S; de Boer, Maarten P
ABSTRACT: There has been a recent resurgence in interest in developing ohmic switches to complement transistors in order to address challenges associated with electrical current leakage. A critical limitation in ohmic switches remains the reliability of their electrical contacts. These contacts are prone to hydrocarbon induced contamination which progressively inhibits signal transmission, eventually leading to device failure. We report on progress made towards controlling the contamination phenomenon. We discuss how contact materials and operating environment affect device performance, showing that RuO2 coated microswitch contacts operating in the presence of O2 experience very limited contaminant accumulation even in hydrocarbon-rich environments. We then demonstrate that devices which have experienced contamination can recover their original performance by being operated in clean N2 :O2 environment. Finally, we suggest that this resistance recovery is associated with the chemical transformation of the contaminant as opposed to its removal and that the transformed contaminant may shield the Pt coating from oxidation.